Status Gizi pada Lansia Pengguna dan Bukan Pengguna Gigi Tiruan - Halim, Dwita N.; Wowor, Vonny N. S.; Wicaksono, Dinar A. (Universitas Sam Ratulangi, 2021)
Abstract: Tooth loss which is often found among elderly may cause problems in mastication. Chewing efficiency may decrease if the elderly do not replace the function of the missing teeth by using dentures. This can further affect their nutritional intake and nutritional status. This study was aimed to explore scientific information regarding differences in elderly nutritional status of removable denture wearers and non-denture wearers. This was a literature review study by searching data on three databases, namely Pubmed, ScienceDirect, and Google Scholar using keywords and a combination of boolean operators. After being selected based on inclusion and exclusion criteria, a critical appraisal was performed, and 10 literatures were obtained consisting of cross-sectional, cohort, and randomized controlled trial design studies. The results showed that the percentage of the elderly with normal nutritional status was higher in denture wearers than in non-denture wearers. There was an increase in nutritional status based on MNA and MNA-SF scores in the elderly after wearing removable dentures. Among elderly, the nutritional status of denture wearers was relatively at risk of malnutrition, while of non-denture wearers was at risk of malnutrition and experienced malnutrition. In conclusion, risk of malnutrition and the occurrence of malnutrition are greater in non-denture wearer elderly.Keywords: nutritional status; elderly; tooth loss; denture wearers; removable denturesÂ Â Abstrak: Kehilangan gigi yang banyak ditemukan pada lansia dapat menyebabkan timbulnya gangguan dalam pengunyahan. Efisiensi kunyah dapat menurun bila lansia tidak menggantikan fungsi gigi asli yang hilang dengan menggunakan gigi tiruan. Hal tersebut dapat berpengaruh terhadap asupan nutrisi dan status gizi lansia. Penelitian ini bertujuan untuk menelaah mengenai perbedaan status gizi pada lansia pengguna dan bukan pengguna gigi tiruan lepasan. Jenis penelitian ialah suatu literature review dengan pencarian data pada tiga database yaitu Pubmed, ScienceDirect, dan Google Scholar menggunakan kata kunci dan kombinasi boolean operator. Setelah diseleksi berdasarkan kriteria inklusi dan eksklusi, dilakukan critical appraisal, dan didapatkan 10 literatur dengan desain studi cross sectional, cohort, dan randomized controlled trial. Hasil penelitian mendapatkan persentase lansia dengan status gizi normal lebih besar ditemukan pada lansia pengguna gigi tiruan daripada lansia bukan pengguna gigi tiruan. Terdapat peningkatan status gizi berdasarkan skor MNA dan MNA-SF pada lansia setelah pemakaian gigi tiruan lepasan. Status gizi lansia pengguna gigi tiruan relatif berisiko malnutrisi, sedangkan pada lansia bukan pengguna gigi tiruan berisiko malnutrisi dan mengalami malnutrisi. Simpulan penelitian ini ialah risiko malnutrisi dan terjadinya malnutrisi lebih besar ditemukan pada lansia bukan pengguna gigi tiruan.Kata kunci: status gizi, lansia; kehilangan gigi; pengguna gigi tiruan; gigi tiruan lepasan